Simultaneous operation of two soft x-ray free-electron lasers driven by one linear accelerator. (20th June 2016) - Faatz, B; Plönjes, E; Ackermann, S; Agababyan, A; Asgekar, V; Ayvazyan, V; Baark, S; Baboi, N; Balandin, V; Bargen, N von; Bican, Y; Bilani, O; et al.
Abstract: Extreme-ultraviolet to x-ray free-electron lasers (FELs) in operation for scientific applications are up to now single-user facilities. While most FELs generate around 100 photon pulses per second, FLASH at DESY can deliver almost two orders of magnitude more pulses in this time span due to its superconducting accelerator technology. This makes the facility a prime candidate to realize the next step in FELs—dividing the electron pulse trains into several FEL lines and delivering photon pulses to several users at the same time. Hence, FLASH has been extended with a second undulator line and self-amplified spontaneous emission (SASE) is demonstrated in both FELs simultaneously. FLASH can now deliver MHz pulse trains to two user experiments in parallel with individually selected photon beam characteristics. First results of the capabilities of this extension are shown with emphasis on independent variation of wavelength, repetition rate, and photon pulse length.